Energy Conservation Practices in Universities Buildings - Hasim, Mohamad Sufian; Wan Azam, Wan Farissa Haslin; Hashim, Ahmad Ezanee; Muhamad Ariff, Nor Rima (Environment-Behaviour Proceedings Journal, 2019)
Energy conservation is one of the significant initiatives towards sustainable campus and should be implemented in university facilities management practices. This research benchmarked for the most effective initiatives and strategies for energy conservation practices in universities. Six (6) semi-structured interview was conducted in three (3) universities organization. The most five (5) effective energy conservation practiced were energy awareness programs in place, adopting energy-efficient appliances and equipment, managing time schedules, implementing the prepaid metering system, and energy management planning. Therefore, the commitments and participation are needed from all universities, both private and public organizations, toward achieving a sustainable future. Keywords: Energy Conservation; Energy Efficiency; Sustainable Facilities Management; Sustainable Universities. eISSN: 2398-4287 Â© 2019. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open-access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v4i12.1899